Kajian Kinerja Keuangan Perusahaan Migas dan Batubara di BEI 2021–2023 Berdasarkan Metode EVA, MVA, dan FVA - Ade Anggara Putra; Ahmad Idris; Trisnia Widuri (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2025)
In facing these dynamics, oil, gas, and coal sub-sector companies are required to design adaptive and flexible business strategies to ensure business continuity, maintain profits, and increase company value. Knowing EVA, MVA, and FVA as financial performance measurement methods that focus on the company's added value can help management. The purpose this study is to determine financial performance using the EVA, MVA, and FVA methods in oil, gas, and coal sub-sector companies listed on the IDX in 2021-2023. This type of research uses quantitative descriptive research. The findings are (1) all companies analyzed showed negative EVA values. This indicates that none 10 companies were able to generate economic profits after deducting their capital costs, (2) only PT Dwi Guna Laksana Tbk consistently posted positive MVA values. This shows that only this company has succeeded in increasing its stock market value sustainably compared to total investment made, (3) only PT Golden Eagle Tbk recorded positive value, indicating the company's ability to create stable and sustainable financial added value. Meanwhile, PT Batu Licin Nusantara Maritim Tbk only recorded positive FVA in 2021, but returned to negative in the following years.